2023
DOI: 10.3389/fmicb.2023.1236497
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and characterization of Staphylococcus aureus isolates from burn wound infections in Fujian, China

Xiaolan Hong,
Shaobo Zhou,
Xubo Dai
et al.

Abstract: BackgroundStaphylococcus aureus (S. aureus) is the most common causative agent of burn wound infection, that often leads to high morbidity and mortality. However, there is not enough knowledge about the molecular epidemiology and antimicrobial susceptibility of S. aureus isolates from burn wound infections in Fujian, China.MethodsBetween 2016 and 2021, 90 S. aureus isolates were collected from burn wound infections in Fujian, China, including 59 methicillin-resistant (MRSA) strains and 31 methicillin-susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The majority of the MRSA isolates belonged to agr I group (89.7%), and 97.8% rifampicin resistance or intermediate isolates assigned to agr I group, moreover, MRSA isolate harbored more virulence genes than MSSA did, which indicated that isolates assigned to agr I group maybe more dangerous and difficult to treat because their chances to be an MRSA carrying more virulence genes were bigger. Recently, an article showed that agr I and agr III group isolates were significantly correlated with burn severity of patients with burn wound infections [ 29 ]. In the other hand, tsst was exclusively found in the MSSA isolates belonging to agr I and agr III groups.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the MRSA isolates belonged to agr I group (89.7%), and 97.8% rifampicin resistance or intermediate isolates assigned to agr I group, moreover, MRSA isolate harbored more virulence genes than MSSA did, which indicated that isolates assigned to agr I group maybe more dangerous and difficult to treat because their chances to be an MRSA carrying more virulence genes were bigger. Recently, an article showed that agr I and agr III group isolates were significantly correlated with burn severity of patients with burn wound infections [ 29 ]. In the other hand, tsst was exclusively found in the MSSA isolates belonging to agr I and agr III groups.…”
Section: Discussionmentioning
confidence: 99%